Tinjauan Mengenai Persahabatan Sejati Berdasarkan Pengkhotbah 4:9-10 di Era Disrupsi - Sariyanto, Sariyanto; Baela, Petrus; Tuminah, Sri; Budi Santoso, Jumadi (Views : Jurnal Teologi dan Biblika, 2025)
The era of disruption, marked by the acceleration of digital technology and globalization, has significantly transformed the way humans interact and build social relationships. While digital technology, including social media, facilitates fast and broad communication, it also presents risks such as rising individualism and social alienation. This study aims to analyze the meaning and urgency of true friendship as reflected in Ecclesiastes 4:9–10 and to evaluate its relevance in addressing social challenges in the digital disruption era. The research employed a qualitative method using an exegetical approach and literature review. The findings reveal that although digital technology enhances virtual connectivity, it cannot replace the need for emotional closeness and meaningful interpersonal engagement. Quality friendship provides essential emotional and spiritual support in navigating modern life pressures. The conclusion of this study emphasizes the need for Christian communities to build relationships grounded in love, loyalty, and honesty. By balancing the use of digital technology with meaningful face-to-face interactions and placing God at the center of relationships, individuals can live a more holistic and harmonious life.